2016
DOI: 10.21921/jas.v3i2.11270
|View full text |Cite
|
Sign up to set email alerts
|

Food Security Status of Assam: A Districts Level Analysis

Abstract: Food security is the foremost important issue of a state or a country. The development of a country or a state is highly dependent on it.Food unsecured population cannot think for other issues of their life. In the state of Assam, just after independence the state had enough food for the population, which gradually decreased until 1981-83. But, after 1981-83, the per capita availability of food grains had increased gradually due to use of modern practices of cultivation viz., high yielding varieties, fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Fresh plant material (fronds) of C. gigantea was collected from Southern Assam. The identification of the fern was done by Miss Kathakali Nath using standard manual [8, 9] and was formally confirmed by Dr. M. K. Bhattacharya. It was also matched with the available herbarium of the species at Central National Herbarium of Botanical Survey of India, Calcutta.…”
Section: Methodsmentioning
confidence: 99%
“…Fresh plant material (fronds) of C. gigantea was collected from Southern Assam. The identification of the fern was done by Miss Kathakali Nath using standard manual [8, 9] and was formally confirmed by Dr. M. K. Bhattacharya. It was also matched with the available herbarium of the species at Central National Herbarium of Botanical Survey of India, Calcutta.…”
Section: Methodsmentioning
confidence: 99%
“…Household food consumption patterns included mainly carbohydrates, protein, fats, vitamins and minerals. Food items considered in the study are shown in Table 2 , and its per capita consumption is shown in Table 3 [ 38 ]. In addition to this, rice is the widely grown cereal crop as a source of carbohydrates, covering over 70 % of the total cultivable area of Assam during the kharif season.…”
Section: Case Studymentioning
confidence: 99%
“…Assam ranks among the country's bottom five states in terms of child survival indicators [1]. With shortages in food production over food consumption, Assam is known to be a 'food-insecure' and 'food-deficit' state [2]. Despite these precedents, the SAM scenario in Assam is largely unknown.…”
mentioning
confidence: 99%